Análise espacial dos casos notificados de sífilis em gestantes no estado da Paraíba - Farias, Cássia Fabiana de Lima Rodrigues (2023)
Syphilis is an infectious and contagious disease with worldwide distribution, whose etiological agent is the bacterium Treponema pallidum. The transmission of this pathological agent can occur in several ways, the most frequent being: unprotected and vertical sexual intercourse from the mother to the fetus. Despite having a quick diagnosis and low-cost treatment, it is still considered a serious public health problem, being categorized as a Sexually Transmitted Infection (STI), which can evolve more seriously, when untreated, leading to impairment of the nervous and cardiovascular system. If the fetus is infected during pregnancy, syphilis can lead to miscarriage, prematurity, stillbirth, early or late congenital manifestations and/or death of the newborn. Objectives: To analyze the spatial dependence of reported cases of syphilis in pregnant women in Paraíba, to determine and analyze the case detection rate over a five-year period (2016 to 2021), to verify the relationship between sociodemographic variables and the outcome of the disease over the course of ten years (2011 to 2021). Method: Mixed ecological study, carried out with secondary data obtained through the Notifiable Diseases Information System (SINAN). Results: In 2016, the detection rate was 4.5/per 1,000 live births, increasing to 15.1/per 1,000 live births in 2021, with an increase of 235.55% in the state's infection rate. The I Moran statistic showed a positive autocorrelation for the years 2018 and 2021 and the sociodemographic aspects pointed to pregnant women: mixed race aged between 20 and 29 and with low education. Conclusion: Low resolution in the basic health network in prenatal care with an exacerbated increase in the number of cases.